Improving postoperative handover: a prospective observational study. - Nagpal, K; Abboudi, M; Manchanda, C; Vats, A; Sevdalis, N; Bicknell, C; Vincent, C; Moorthy, K (2013)
BACKGROUND: The information provided during the postoperative handover influences the delivery of care of patients in the postoperative recovery unit through their care on the ward. There is a need for a structured and systematic approach to postoperative handover. The aim of this study was to improve postoperative handover through the implementation of a new handover protocol, which involved a handover proforma and standardization of the handover process. METHODS: This prospective pre-post intervention study demonstrated the improvement in postoperative handover through standardization. There was a significant reduction in information omissions and task errors and improvement in communication and teamwork with the new handover protocol. RESULTS: There was a significant reduction in overall information omissions from 9 to 3 (P < .001) omissions per handover and task errors from 2.8 to .8 (P < .001) with the new handover protocol. Teamwork and nurses' satisfaction score significantly improved from a median of 3 to 4 (P < .001) and median of 4 to 5 (P < .001). Duration of handover decreased from a median of 8 to 7 minutes (P < .376). CONCLUSIONS: The study demonstrates that standardization of postoperative handover improved communication and teamwork and reduced information omissions and task errors. There was an improvement in the quality of the handover after the introduction of the new handover protocol, which was easy and simple to use.